Biomimetic cork-based CeO2 ecoceramics for hydrogen generation using concentrated solar energy - Pullar R.C., Gil L., Oliveira F.A.C.
Naturally occurring and sustainable materials can be used as a template to create biomimetic/biomorphic ceramics, known as Ecoceramics (environmentally conscious ceramics). In this work, cork was chosen as template to produce novel ceria (CeO2) ecoceramics, for applications in water splitting for H2 production via direct concentrated solar thermochemical fuel production (TCFP). The cork powder was pyrolised at 900 çC and the resulting carbon skeleton was infiltrated with an aqueous CeO2 precursor, and then heated at 1000 çC for 2 h to produce the ecoceramic. The cellular structure of the cork was maintained, with hexagonal cell dimensions of 20-30 _m in diameter, but the grains were nanoscale at _100 nm. XRD data confirmed that CeO2 was the only crystalline phase obtained. An important feature was that, while the rectangular side walls were maintained to hold the three-dimensionally ordered macroporous (3DOM) cellular cork structure, the rear hexagonal walls were pierced repeatedly through the structure, unlike in the original cork structure, which will allow gasses such as H2 to permeate well into the structure, greatly increasing the reactive area available for catalysis. The next step will be to test the capabilities of both the regular, porous 3DOM structure and the nanoscale grains for thermochemical water splitting to produce hydrogen under direct concentrated solar energy. © 2016 Portuguese Society of Materials (SPM)